Anti-SARS-CoV-2 Biotherapeutics and Chemotherapeutics: An Insight into Product Specifications and Marketing Dynamics - Vijay, Kotra; Mallem, Dinakar; Anil Kumar, Kanuri; Mahesh Reddy, Burra; Shaik, Nyamathullah; Ying, Looi Shu; Khairul Anwar, Husain; Vrala, Ravi; Sudhakar, Madhavedi; Goh, Khang Wen; Sam, Toong Hai; Long, Chiau Ming * (HH Publisher, 2022)
Chemotherapeutics and biotherapeutics agents have been explored as a potential treatment for COVID-19. This study was aimed to elucidate latest update related to biotherapeutics and chemotherapeutics against COVID-19 and its variants as well as the product specifications and marketing dynamics of its pharmacotherapies. There are several chemotherapeutics that have been studied for the treatment of COVID-19, including Paxlovid (Nirmatrelvir & Ritonavir) fixed dose combination, nirmatrelvir and ritonavir fixed dose combination, Remdesivir (Vekulary/Covifor) fixed dose combination, chloroquine and hydroxychloroquine, molnupiravir, favipiravir, Infliximab (Remsima®) fixed dose combination tocilizumab (Actimera), casirivimab+imdevimab (Ronapreve) fixed dose combination, ivermectin, methylprednisole. These drugs have been repurposed for use in COVID-19 due to their antiviral properties and ability to reduce inflammation. The COVID-19 death cases have significantly reduced because of tested efficacy of advanced biotherapeutics and chemotherapeutics. As for marketing dynamics, the demand for chemotherapeutics for the treatment of COVID-19 has increased significantly since the outbreak of the pandemic. Hence, the prices of anti-viral and monoclonal antibodies in top COVID-19 affected countries is also presented here. Considering the molecular interactions, therapeutic activity, efficacy, and adverse effects, the USFDA and the WHO recommended the aforementioned drugs. The chances of approval seems favouring biotherapeutics as these have the best characteristics among the chemotherapeutics. Overall, this review contributes to the scientific understanding of the COVID-19. This can help to inform future research and development efforts and contribute to the overall advancement of knowledge in the field of medicine. © 2022, HH Publisher. All rights reserved.